A study on the relationship between industry concentration and stock returns the Philippine case - Fernandez, Miguel Carlos A. (School of Economics, University of the Philippines Diliman, 2018)
The Philippines is largely dominated by a few companies exercising considerable market power, begging the question How does market concentration affect returns to investment. While higher market concentration is often associated with higher R and D expenditures, and thus, greater technological improvement and more innovation, the literature identifies two channels of risk _ innovation risks and macroeconomic risks _ associated with industry concentration that might adversely affect returns to investment. Using Fama_Macbeth regressions, this paper analyzes the effects of industry concentration on the average stock returns, using Philippine Stock Exchange monthly data on 88 publicly_listed firms from January 2009 to December 2017. This paper finds that more concentrated industries tend to face less risks as compared to more competitive industries. By having less exposure to these risks, average stock returns tend to decrease, even after controlling for size, book-to-market ratio, momentum and the other usual determinants of average stock returns. Furthermore, firms in more concentrated industries tend to be more insulated from macroeconomic risks.